Psychological well-being and associated factors among parents of adolescents with non-suicidal self-injury: a cross-sectional study - Xia, Qian; Zhang, Yan; Huang, Xuehua (Frontiers in Psychiatry, 2023)
Background: Non-suicidal self-injury (NSSI) impacts not only adolescents who engage in it but also their parents. However, there has been limited research into the psychological well-being of these parents. This cross-sectional study aims to investigate the symptoms of anxiety and depression among parents of adolescents who engaged in NSSI in China and the factors associated with them. Methods: A total of 400 parents of adolescents with NSSI were included. Socio-demographic information of these parents was collected. The Generalized Anxiety Disorder 7-item (GAD-7), the Patient Health Questionnaire 9-item (PHQ-9), and the Connor-Davidson Resilience Scale (CD-RISC) were used to assess symptoms of anxiety, depression, and psychological resilience, respectively. Results: The majority of the parents were female (83.5%), married (86.3%), and had a senior high school or equivalent and lower education level (67.1%). The study found that 35.3% of the parents experienced clinically significant symptoms of anxiety (GAD-7 ≥ 7) and 40.1% had clinically significant symptoms of depression (PHQ-9 ≥ 7). Parents with larger ages and lower levels of psychological resilience were more likely to experience symptoms of anxiety and depression (p < 0.05). Parents who reported bad parent-child relationships showed a higher level of anxiety. Conclusion: This study provides important insights into the symptoms of anxiety and depression among parents of adolescents with NSSI. Parental age, parent-child relationship, and psychological resilience were associated with symptoms of anxiety and depression in these parents. Implications for the development of interventions aimed at addressing symptoms of anxiety and depression in parents of adolescents with NSSI were discussed.